2008
DOI: 10.1016/j.jvs.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of action of pneumatic compression devices: Combined magnetic resonance imaging and duplex ultrasound investigation

Abstract: This methodology provides means for the investigation of relationships between the pressure in the garment, interface pressure, tissue deformation, and hemodynamic respond to IPC. The clinical efficacy of IPC should not be explicitly attributed to the magnitude of the pressure in the garment. Similar hemodynamic responses to IPC can be produced by different spatial distributions of pressure resulting in different patterns of tissue compression. Further investigation of biomechanical mechanisms of IPC is needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Studies have shown that IPC of the lower limbs may improve venous blood flow in the venous system and increase fibrinolytic activity. 51,82 Thus, it is perhaps not surprising to observe that IPC is more effective than no prophylaxis or TEDS in reducing venous thromboembolism. Using IPC alone, however, may not be completely effective in preventing thromboembolism in high-risk patients, combined use of IPC and pharmacological thromboprophylaxis can tackle both venous stasis and hypercoagulability simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IPC of the lower limbs may improve venous blood flow in the venous system and increase fibrinolytic activity. 51,82 Thus, it is perhaps not surprising to observe that IPC is more effective than no prophylaxis or TEDS in reducing venous thromboembolism. Using IPC alone, however, may not be completely effective in preventing thromboembolism in high-risk patients, combined use of IPC and pharmacological thromboprophylaxis can tackle both venous stasis and hypercoagulability simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of stasis is a main goal in CVD treatment and decisive in preventing venous complications and is frequently done through conservative approaches. Conservative CVD treatment might include intermittent pneumatic compression [116], compression stockings and bandages [77,117,118], and muscle pump activation using electrical muscle stimulation [77,119], transcutaneous electrical nerve stimulation [119], or active and passive movements [103,119]. In this regard, MLD maneuvers may be an alternative treatment to enhance venous flow [21][22][23].…”
Section: Conservative Treatment Of Cvdmentioning
confidence: 99%
“…Lurie et al 17 used MRI and Duplex ultrasound to clarify the mode of action of intermittent pneumatic compression, which is more complex to assess than permanent compression. They found a measurable decrease in the volume of subcutaneous tissue under the garment.…”
Section: For the Future: A Numerical Approach And Simulation By Finitmentioning
confidence: 99%